2023
DOI: 10.1073/pnas.2206694120
|View full text |Cite
|
Sign up to set email alerts
|

lncRNA BREA2 promotes metastasis by disrupting the WWP2-mediated ubiquitination of Notch1

Abstract: Notch has been implicated in human cancers and is a putative therapeutic target. However, the regulation of Notch activation in the nucleus remains largely uncharacterized. Therefore, characterizing the detailed mechanisms governing Notch degradation will identify attractive strategies for treating Notch-activated cancers. Here, we report that the long noncoding RNA (lncRNA) BREA2 drives breast cancer metastasis by stabilizing the Notch1 intracellular domain (NICD1). Moreover, we reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 66 publications
0
11
0
Order By: Relevance
“…Utilizing CTG, colony formation assays, and scratch assays, we observed that Linc01135 enhances the proliferative and migratory capabilities of gastric cancer cells. Furthermore, numerous studies have argued that that long noncoding RNAs (lncRNAs) associate with protein partners exerting an important impact in cancer [49][50][51][52]. Therefore, we operate RNA Pulldown and RIP experiments confirmed the specific binding between Linc01135 and CDC45 while FISH combined with immunofluorescence demonstrated their co-localization within the cell nucleus.…”
Section: Discussionmentioning
confidence: 72%
“…Utilizing CTG, colony formation assays, and scratch assays, we observed that Linc01135 enhances the proliferative and migratory capabilities of gastric cancer cells. Furthermore, numerous studies have argued that that long noncoding RNAs (lncRNAs) associate with protein partners exerting an important impact in cancer [49][50][51][52]. Therefore, we operate RNA Pulldown and RIP experiments confirmed the specific binding between Linc01135 and CDC45 while FISH combined with immunofluorescence demonstrated their co-localization within the cell nucleus.…”
Section: Discussionmentioning
confidence: 72%
“…The classic lysosomal pathway is often associated with autophagy and apoptosis, but in stable MR‐1‐ knockdown H1299 cells, it did not cause the changes of autophagy markers (p62) and apoptosis markers (PARP and caspase3) through Western blot. The degradation mode of NICD3 is different from that of NICD1 and NICD2, [ 44 , 45 , 46 ] which may be related to the number and position of lysine residues in the NICD3 sequence. [ 47 ] We conducted sequence alignment of NICD1‐3 through Cluster X2.1, which was visualized by GeneDoc, and found that only 21 lysine residues were present in the NICD3 sequence, and compared to NICD1 and 2, there were no lysine dense regions (Figure S7 , Supporting Information, 400–450).…”
Section: Resultsmentioning
confidence: 99%
“…LncRNA, with a length exceeding 200 nucleotides, is regarded as a type of RNA that cannot encode and translate into proteins and exerts a variety of functions on regulating lung metastasis of breast cancer 87 . It has been well documented that lncRNA BREA2 is able to suppress the formation of WWP2-NICD1 complex, thereby stabilizing NICD1 to strengthen the transduction of Notch signals and further accelerate the lung metastasis of breast cancer 88 . In addition, the overexpression of lncRNA ROR in the epithelial cells of breast cancer is prone to orchestrate the process of EMT through repressing the degradation of miR-205 target genes, which paves the way for exacerbating the lung metastasis of breast cancer.…”
Section: Roles Of Fibroblasts Of Metastatic Organ In Pmn Formationmentioning
confidence: 99%